Electrodeposition and electroless plating of hierarchical metal superstructures composed of 1D nano- and microscale building blocks. (1st June 2016) - Muench, Falk; Felix, Eva-Maria; Rauber, Markus; Schaefer, Sandra; Antoni, Markus; Kunz, Ulrike; Kleebe, Hans-Joachim; Trautmann, Christina; Ensinger, Wolfgang
Graphical abstract: Highlights: hierarchical nanostructured metal architectures deposited in track etched membranes. superstructures composed of 1D building blocks: nanowires, -tubes, -rods, microwires. electroless plating: (tube-on-tube), (wire-on-tube) and (rod-on-tube) assemblies. electrodeposition: (wire-on-wire) assemblies. free-standing hierarchical assemblies display promising unsupported electrocatalysts. Abstract: The fabrication of ordered superstructures composed of nano- and microscale building blocks is of tremendous interest. In this work, we present a versatile approach for the synthesis of hierarchical and free-standing metal architectures of high structural complexity. Using the ion-track etching technique, hierarchically porous polycarbonate membranes are obtained, which are employed as nanocasting templates. Pore filling is accomplished by the two complementary wet-chemical techniques electrodeposition and electroless plating. Depending on the pore filling mechanism and the template structure, a wide range of novel metal nano-/micro-architectures can be realized. The products can be characterized as hierarchical assemblies of 1D structures (nanotubes, nanowires, microwires, nanorods). With electrodeposition, complete pore filling is achieved, which results in the formation of wire-based morphologies. Special attention is dedicated to the controlled partial filling of the pores with electroless plating, which allows the simultaneous deposition of tubes and – depending on the conformity of the plating reaction and the deposition time – narrower arrays of tubes, wires or rods. To demonstrate the favorable functional properties of the obtainable products, a silver-based wire-tube assembly is employed in the enzyme-free and selective electrochemical detection of hydrogen peroxide. An excellent sensitivity of 1340 μA mM −1  cm −2 and a fast response time of <2 s is achieved, which is explained by the absence of binders, the well-accessible, open-pored structure, the presence of continuous conduction pathways and the high surface area of the material.